Evolution [videorecording (DVD)] - Reitman, Ivan; Duchovny, David; Moore, Julianne; Powell, John, 1963- (DreamWorks Home Entertainment, 2001)
When aliens emerge from a meteorite that has landed on earth it is up to Doctors Kane, Reed and Block, along with some unlikely companions to stop them from taking over the planet earth.